The Effects of Bark Biochar Absorbent in Bagasse Litter on the Litter Quality and Weight of the Digestive Organs of Broiler Chickens - Alfarizi, Muhammad; Berliana; Azis, Abdul; Nurhayati; Nelwida (Faculty of Animal Science, Universitas Brawijaya, 2025)
Plantation waste, such as bagasse, is an alternative substitute for wood shavings as a litter for broiler chickens. However, it is difficult for bagasse to release moisture, so an absorbent material is needed to improve the quality of litter that is prone to moisture. This study aimed to determine the effects of the use of an absorbent from bark biochar on bagasse litter quality and the weight of the digestive organs of broiler chickens. This study used 200 Lohmann strain broiler chicks. The feeds used consisted of 2 types, namely, BR-1 and BR-2. The thickness of the litter spread in each treatment was 5 cm, and the amount given was based on the bulk density of the litter material (kg/m3). There were 5 levels of biochar as an adsorbent for bagasse litter: P-0: 0% biochar (control); P-1: 5% biochar; P-2: 10% biochar; P-3: 15% biochar; and P-4: 20% biochar. A completely randomized design (CRD) was used in the experimental design. The results of the analysis of variance revealed that the addition of biochar had no significant effect on the litter moisture, feed intake, slaughter weight, or digestive organ weight of broiler chickens. It was concluded that the addition of biochar as an absorbent up to 20% in bagasse litter did not affect the weight of the digestive organs of broiler chickens.